Association between maternal sleep practices and late stillbirth – findings from a stillbirth case‐control study. (20th November 2017) - Heazell, AEP; Li, M; Budd, J; Thompson, JMD; Stacey, T; Cronin, RS; Martin, B; Roberts, D; Mitchell, EA; McCowan, LME
Abstract : Objective: To report maternal sleep practices in women who experienced a stillbirth compared with controls with ongoing live pregnancies at similar gestation. Design: Prospective case‐control study. Setting: Forty‐one maternity units in the United Kingdom. Population: Women who had a stillbirth after ≥ 28 weeks' gestation (n = 291) and women with an ongoing pregnancy at the time of interview (n = 733). Methods: Data were collected using an interviewer‐administered questionnaire that included questions on maternal sleep practices before pregnancy, in the four weeks prior to, and on the night before the interview/stillbirth. Main outcome measures: Maternal sleep practices during pregnancy. Results: In multivariable analysis, supine going‐to‐sleep position the night before stillbirth had a 2.3‐fold increased risk of late stillbirth [adjusted Odds Ratio (aOR) 2.31, 95% CI 1.04–5.11] compared with the left side. In addition, women who had a stillbirth were more likely to report sleep duration less than 5.5 hours on the night before stillbirth (aOR 1.83, 95% CI 1.24–2.68), getting up to the toilet once or less (aOR 2.81, 95% CI 1.85–4.26), and a daytime nap every day (aOR 2.22, 95% CI 1.26–3.94). No interaction was detected between supine going‐to‐sleep position and a small‐for‐gestational‐age infant, maternal body mass index, or gestational age. The population‐attributable risk for supine going‐to‐sleep position was 3.7% (95% CI 0.5–9.2). Conclusions: This study confirms that supine going‐to‐sleep position is associated with late stillbirth. Further work is required to determine whether intervention(s) can decrease the frequency of supine going‐to‐sleep position and the incidence of late stillbirth. Tweetable abstract: Supine going‐to‐sleep position is associated with 2.3× increased risk of stillbirth after 28 weeks' gestation. Plain Language Summary: Stillbirth, the death of a baby before birth, is a tragedy for mothers and families. One approach to reduce stillbirths is to identify factors that are associated with stillbirth. There are few risk factors for stillbirth that can be easily changed, but this study is looking at identifying how mothers may be able to reduce their risk. In this study, we interviewed 291 women who had a stillbirth and 733 women who had a live‐born baby from 41 maternity units throughout the UK. The mothers who had a stillbirth were interviewed as soon as practical after their baby died. Mothers who had a live birth were interviewed during their pregnancies at the same times in pregnancy as when the stillbirths occurred. We did not interview mothers who had twins or who had a baby with a major abnormality. Mothers who went to sleep on their back had at least twice the risk of stillbirth compared with mothers who went to sleep on their left‐hand side. This study suggests that 3.7% of stillbirths after 28 weeks of pregnancy were linked with going to sleep lying on the back. This study also shows that the link between going‐to‐sleep position and late stillbirth was not affected by the duration of pregnancy after 28 weeks, the size of the baby, or the mother's weight. Women who got up to the toilet once or more at night had a reduced risk of stillbirth. This is the largest of four similar studies that have all shown the same link between the position in which a mother goes to sleep and stillbirth after 28 weeks of pregnancy. Further studies are needed to see whether women can easily change their sleep position in late pregnancy and whether changing the position a mother goes to sleep in reduces stillbirth. Abstract : Tweetable abstract Supine going‐to‐sleep position is associated with 2.3× increased risk of stillbirth after 28 weeks' gestation. This paper includes Author Insights, a video abstract available athttps://vimeo.com/rcog/authorinsights14967